UNDERSTANDING: THE NURTURE OF NATURE - PART 1 - Miller, Ronald (PINS-Psychology in Society, 2026)
It is a curious and intriguing feature of Psychology that understanding does not feature as a topic or name a class of events or even signify a concept deserving of explanation in a discipline concerned with mind matters. We don’t seem to mind that understanding matters and that in the same way that psychology is a reflexive discipline providing explanations for the minds that must explain mind so too does our understanding turn on itself and beg questioning. The spaces between attention, perception, learning, intelligence, thinking, language, problem solving, and information processing, provide convenient joints for the carving of Cognitive Psychology into manageable pieces and it is in the carving that understanding seems to disappear into these empty spaces. More recently the pieces have been put back together and combined with computer and brain sciences producing a new Cognitive Science for the new millennium. On the flanks of this new hyper-science are linguistics, evolutionary biology/psychology and robotics, and riding along with the crew are the metaphysicians keeping the score, administering Turing tests, demolishing the Theatre that Rene built (and banishing the phantom within), and devising thought experiments involving brains in vats, bats, and Chinese rooms. This new Cognitive Science seems to stand in an awkward relation to Psychology appropriating its cognitive bits for itself while exposing itself to counter revolutionary forces that would re-incorporate it within the larger whole that is conveyed by the term Psychology. Although it may be convenient and politic within the academy for researchers to hive off and proclaim a new terrain or dominion to attract funds and prestige, the form of the new cognitive science seems to bear a strong resemblance to that of the old psychology inaugurated by the early pioneers such as Helmholtz, Wundt, James, Baldwin, Pavlov, and Ebbinghaus, to mention but a few. At its inception, Psychology consisted of a heady brew fermented out of physiology laboratories and philosophical armchairs. Instead of the boot-up electronic digital machine that underpins our current post-modern computation model of mind, the old Psychology was moulded in the image of a wind-up hydraulic analogue machine. And in much the same way that the founding figures tried to distil consciousness out of their machine (or pump out un consciousness), so too has consciousness been resurrected as a possible jewel in the reigning crown of Cognitive Science. It is interesting that contemporary consciousness researchers such as Dennett (1993) and Flanagan (1992) refer all the way back to James, and that Luria and Vygotsky’s work in the early part of the 20th century is cited as providing examples of what today is called distributed cognition (Clark, 1997). Certainly, Piaget’s epistemic subject that operates with modular logical (computational) models seems a possible contender for the as yet unspecified subject of Cognitive Science.